METAFICTIONAL TECHNIQUES IN LAURENCE STERNE‘S TRISTRAM SHANDY ANDJOHN BARTH‘S LOST IN THE FUNHOUSE (International Journal of Food and Nutritional Sciences, 2022)
The thesis compares and contrasts the forms and purposes of metafictional modes used in Laurence Sterne's work Tristram Shandy and John Barth's short storey collection Lost in the Funhouse. The goal is accomplished by employing textual analysis and comparative approaches, as well as studying and presenting an overview of metafiction as a literary device, critical reviews of Laurence Sterne's and John Barth's philosophic and aesthetic preferences, and a general historical, philosophical, and literary background of postmodernism and the eighteenth century. Despite the two-century gap, the analytical section of the paper, which consists of two chapters, each presenting various modes and functions of typographic and non-typographic metafictional means, revealed a great deal of similarity between the two works. In terms of the visual play of the text, the concentration on the divergence between art and life, and the portrayal of the roles of narrator and narratee, the fictions are strikingly similar. Barth and Sterne talk of current authors' literary stasis, in which they are unable to depict the complexity, fragmentariness, and solitude of a modern illogical human using previously existent conventional literary tools. The approach is to utilise a collage of a number of literary genres, styles, and methods that allow its readers a broad range of interpretation options so that the narratees may impart their own meanings. The metafictional figure Tristram Shandy, on the other hand, differs from Lost in the Funhouse in terms of its conversational approach to readers, physical handling of tales, metafictional analogies, and the amount of particular metafictional tactics used in the works.